Simplified method to quantify valve back‐leak uncovers severe mesenteric lymphatic valve dysfunction in mice deficient in connexins 43 and 37 - Castorena‐Gonzalez, Jorge A.; Srinivasan, R. Sathish; King, Philip D.; Simon, Alexander M.; Davis, Michael J. (The Journal of physiology, 2020)
Key points Lymphatic valve defects are one of the major causes of lymph transport dysfunction; however, there are no accessible methods for quantitatively assessing valve function. This report describes a novel technique for quantifying lymphatic valve back‐leak. Postnatal endothelial‐specific deletion of connexin 43 (Cx43) in connexin 37 null (Cx37−/−) mice results in rapid regression of valve leaflets and severe valve dysfunction. This method can also be used for assessing the function of venous and lymphatic valves from various species, including humans. The lymphatic system relies on robust, spontaneous contractions of collecting lymphatic vessels and one‐way secondary lymphatic valves to efficiently move lymph forward. Secondary valves prevent reflux and allow for the generation of propulsive pressure during each contraction cycle. Lymphatic valve defects are one of the major causes of lymph transport dysfunction. Genetic mutations in multiple genes have been associated with the development of primary lymphoedema in humans; and many of the same mutations in mice result in valve defects that subsequently lead to chylous ascites or chylothorax. At present the only experimental technique for the quantitative assessment of lymphatic valve function utilizes the servo‐null micropressure system, which is highly accurate and precise, but relatively inaccessible and difficult to use. We developed a novel, simplified alternative method for quantifying valve function and determining the degree of pressure back‐leak through an intact valve in pressurized, single‐valve segments of isolated lymphatic vessels. With this diameter‐based method, the competence of each lymphatic valve is challenged over a physiological range of pressures (e.g. 0.5–10cmH2O) and pressure back‐leak is extrapolated from calibrated, pressure‐driven changes in diameter upstream from the valve. Using mesenteric lymphatic vessels from C57BL/6J, Ub‐CreERT2;Rasa1fx/fx, Foxc2Cre/+, Lyve1‐Cre;Cx43fx/fx, and Prox1‐CreERT2;Cx43fx/fx;Cx37−/− mice, we tested our method on lymphatic valves displaying a wide range of dysfunction, from fully competent to completely incompetent. Our results were validated by simultaneous direct measurement of pressure back‐leak using a servo‐null micropressure system. Our diameter‐based technique can be used to quantify valve function in isolated lymphatic valves from a variety of species. This method also revealed that haplodeficiency in Foxc2 (Foxc2Cre/+) is not sufficient to cause significant valve dysfunction; however, postnatal endothelial‐specific deletion of Cx43 in Cx37−/− mice results in rapid regression of valve leaflets and severe valve dysfunction. Key points Lymphatic valve defects are one of the major causes of lymph transport dysfunction; however, there are no accessible methods for quantitatively assessing valve function. This report describes a novel technique for quantifying lymphatic valve back‐leak. Postnatal endothelial‐specific deletion of connexin 43 (Cx43) in connexin 37 null (Cx37−/−) mice results in rapid regression of valve leaflets and severe valve dysfunction. This method can also be used for assessing the function of venous and lymphatic valves from various species, including humans.